2009
DOI: 10.1016/j.joca.2008.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Attempt to replicate published genetic associations in a large, well-defined osteoarthritis case–control population (the GOAL study)

Abstract: Lack of replication is common and could be due to differences in study design, phenotype, populations examined or the occurrence of false positives in the initial study. Variants within TGFB1, IGF1 and IL1RN could have a role in OA susceptibility; however, replication of these findings is required in an independent study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 31 publications
1
38
1
Order By: Relevance
“…Further, certain association between rs3740199 SNP in the ADAM12 gene and radiographic knee OA or presence of osteophytes in TFJ was observed in a Chingford Study cohort study (women aged 47-63 years, N = 749), but this association was failed to replicate in GOAL study (1,040 cases with clinical knee OA from orthopaedic surgery lists, Nottingham, UK) [8]. However, our previous work showed that the rs3740199 ADAM12 gene was linked to the presence of osteophytes of both joints in the whole investigated group and to OA in the PFJ in men [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, certain association between rs3740199 SNP in the ADAM12 gene and radiographic knee OA or presence of osteophytes in TFJ was observed in a Chingford Study cohort study (women aged 47-63 years, N = 749), but this association was failed to replicate in GOAL study (1,040 cases with clinical knee OA from orthopaedic surgery lists, Nottingham, UK) [8]. However, our previous work showed that the rs3740199 ADAM12 gene was linked to the presence of osteophytes of both joints in the whole investigated group and to OA in the PFJ in men [7].…”
Section: Discussionmentioning
confidence: 99%
“…ADAM12 has been shown to be implicated in a variety of human diseases, such as Down's syndrome [3], breast, bladder, liver and lung cancers [4], as well as cardiac hypertrophy [5]. ADAM12 gene has also been observed to be associated with the development of knee osteoarthritis (OA) [6,7], but a recent study was unable to replicate this association [8].…”
Section: Introductionmentioning
confidence: 99%
“…Approval for the study was obtained from the Nottingham Research Ethics Committee. Study recruitment occurred from 2002 to 2006 (21).…”
Section: Methodsmentioning
confidence: 99%
“…To do this, we investigated the participants in the Genetics of Osteoarthritis and Lifestyle (GOAL) case-control study. This wellcharacterized group was primarily established for studying the genetic-environmental interaction in people with symptomatic, clinically severe knee and hip OA (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…GOAL study [27] utilized large number of symptomatic radiographic knee or hip OA and controls to replicate 68 variants in 12 genes including IL1A, IL1B, IL1RN, IL4R, IL6, COL2A1, ADAM12, ASPN, IGF1, TGFB1, ESR1 and VDR, but they did not replicate any of these associations. All the genetic variants they studied were included in our study.…”
Section: Discussionmentioning
confidence: 99%